Peer to Peer Lending Sebagai Alternatif Penyaluran Pembiayaan Lembaga Keuangan Mikro - Trinov Gira Thimoteus Sihite; Akhmad Budi Cahyono (Jurnal Analisis Hukum, 2022)
The regulation and supervision of the distribution of capital in a Microfinance Institution is currently still not running optimally considering that there are still many entities that have limited operational capital to develop their businesses. This encourages an innovation for those who are careful in seeing economic opportunities, one of which is Fintech Lending. Fintech as one of the digital pioneers that can accelerate economic turnover and facilitate financial transactions, including access to funding for the public. It is hoped that the disruption of technology can increase competition among financial services business players in Indonesia. The purpose of this study is to determine the presence and function of Fintech Lending as an alternative source of financing solutions for Microfinance Institutions who are experiencing capital difficulties to do business, and to provide understanding to Microfinance Institutions regarding preventive and repressive legal protection if one day a Microfinance Institution enter into a cooperation agreement to conduct a microfinance project. The research method used is normative, namely through literature review/legal documents. The results of the study show that Fintech Lending can collaborate with Microfinance Institutions to realize equitable distribution of the people's economy.